Вплив умов спікання на структуроутворення композиційних матеріалів на основі вольфраму - Мініцький, А. В.; Ямшинський, М. М.; Биба, Є. Г.; Мініцька, Н. В.; Поліщук, К. В.; Лук’яненко, І. В.; Кивгило, Б. В. (Physico-technological Institute of Metals and Alloys, 2023)
The use of heavy tungsten alloys is essential for many industries, as these alloys are ideal for a variety of products due to their high density. The main problem in creating such alloys is the need to use high sintering temperatures, which significantly complicates the technology of producing tungsten alloys. To reduce the sintering temperatures of tungsten alloys, alloying elements are added to their composition to activate sintering processes at lower temperatures (nickel, iron and copper). The main task in forming the structure and properties of tungsten-based alloys is to ensure sintering conditions in the presence of the liquid phase, which contributes to the formation of a strong framework in the material structure and high density of the composite. Various methods of producing tungsten-based alloys have been investigated and the influence of the chemical composition of alloying additives on the sintering process conditions has been studied. The effect of pressing and post-pressing pressure on the porosity of tungsten-based molds was determined. It is shown that in the pressure range of 200-700 MPa, the maximum compaction of tungsten powder occurs at pressures of 500-550 MPa, which provides porosity at the level of 35-37 %. The difference between the sintering mechanisms of W-Ni and W-Fe systems at a temperature of 1350 ºC, which is sufficient for liquid-phase sintering with a nickel bond, and low for an iron bond, is shown. The process of infiltration of a porous tungsten alloy framework with copper melt obtained from metal-working waste was studied. The conditions that ensure complete impregnation of the tungsten framework with copper at a temperature of 1200 ºC and allow to obtain a porous material are determined. The results of the work can be used to create tungsten-based products with high specific gravity and density, including from metalworking waste, which significantly reduces the cost of such materials.